Leaving a Man: Javanese Female Resistance in Indonesian Folktales and Songs - Harjito; María Capetillo Lozano (Estudios de Asia y África, 2021)
Marriage is an intrinsic part of the life cycle around the world, and Javanese culture is no exception. However, it causes many problems in relationships between women and men. This research explores how Javanese women put up resistance through the analysis of stories and songs. It also reveals that they choose their husbands based on certain criteria, and leave them when the men fall short of their expectations. This non-fulfilment often happens because the original choice was based on the man’s personality or appearance, or even due to an unplanned affair. Giving up that relationships allows women to achieve freedom and recover their rights as individuals. These folk stories and songs offer a form of catharsis for Javanese women, who, for economic, social and cultural reasons, lack opportunities to leave their husbands.